Korean Red Ginseng Pretreatment Protects Against Long-Term Sensorimotor Deficits After Ischemic Stroke Likely Through Nrf2 - Liu, Lei; Vollmer, Mary K.; Fernandez, Victoria M.; Dweik, Yasmin; Kim, Hocheol; Doré, Sylvain (Frontiers in Cellular Neuroscience, 2018)
Endogenous neuroprotective mechanisms by which the brain protects itself against noxious stimuli and recovers from ischemic damage are key targets of stroke research, ultimately facilitating functional recovery. Transcriptional factor Nrf2, enriched in astrocytes, is a master regulator of endogenous defense systems against oxidative stress and inflammation. Korean Red Ginseng (Ginseng), one most widely used herbal medicine, has exhibited promising potentials in neuroprotection. Our study aimed to determine whether the standardized Ginseng extract pretreatment could attenuate acute sensorimotor deficits and improve long-term functional recovery after ischemic stroke though Nrf2 pathway and whether reactive astrogliosis is associated with such effect. Adult Nrf2-/- and matched wildtype control (WT) mice were pretreated with Ginseng orally for 7 days prior to permanent distal middle cerebral artery occlusion (pdMCAO). Using an optimized method that can accurately assess either severe or mild pdMCAO-induced sensorimotor deficits, neurobehavioral tests were performed over 28 days. The progression of lesion volume and the evolution of astrocytic and microglial activation were determined in the acute stage of ischemic stroke after pdMCAO (0-3 days). Nrf2-downstream target antioxidant genes expression levels was assessed by Western blot. We found that Ginseng pretreatment ameliorated acute sensorimotor deficits and promoted long-term functional recovery, prevented the acute enlargement of lesion volume (36.37±7.45% on day 3), attenuated reactive astroglial progression but not microglia activation, and enhanced the induction of Nrf2-downstream target proteins after ischemic insult in WT mice, an effect which was lost in Nrf2 knockouts. The spatiotemporal pattern of reactive astrogliosis evaluation correlated well with acute ischemic damage progression in an Nrf2-dependent fashion during the acute phase of ischemia. In contrast, Nrf2 deficiency mice exhibited exacerbated ischemic condition compared to WT controls. Together, Ginseng pretreatment protects against acute sensorimotor deficits and promotes its long-term recovery after pdMCAO, at least partly, through Nrf2 activation, highlighting the potential efficacy of oral consumption of Ginseng for stroke preventative intervention in patients who are at great risk of recurrent stroke or transient ischemic attack. The attenuated reactive astrogliosis contributes to the Nrf2 pathway related neuroprotection against acute ischemic outcome and substantially long-term sensorimotor deficits in the context of ischemic stroke under pdMCAO.